Attitudes of Malaysian extension workers towards sustainable agricultural practices - Tiraieyari, Neda; Hamzah, Azimi; Abu Samah, Bahaman; Uli, Jegak (Science Publications, 2013)
The challenge of producing enough food for growing population increasingly affected Malaysian agricultural sector. Intensive farming system and increase in fertilizer used by farmers has led the agricultural sector to some environmental damage. The Department of Agriculture (DOA) has earmarked Sustainable Agricultural Practices (SAP) to transfer unsustainable agriculture into a sustainable manner. The SAP should be transferred by extension workers to the farmers. However little is known about Malaysian extension workers’ attitudes towards SAP. Front line extension workers in the DOA were surveyed to identify their attitudes on SAP. A descriptive research design was used to collect data from 400 extension workers. Results revealed that extension workers have positive attitudes on SAP concepts. It is recommended to find out to what extent extension workers attitudes has played significant role to transfer information to the farmers.